Effectiveness Of Rebozo Technique And Massage Counter Technique On Labor Pain In Active Phase 1 At Pmb Bd Itoh 2023 - Neni Sri Wahyuni; Feva Tridiyawati (CV. Inara, 2024)
Background: Labor pain is a subjective experience of physical sensations associated with uterine contractions, cervical dilatation and effacement, and fetal descent during labour. Labor pains begin during the first incubation period and continue into the active phase. Labor pain can be controlled by non-pharmacological methods, rebozo techniques and massage counters. Research Objectives: To determine the effectiveness of the rebozo technique and counter massage technique for active phase 1 labor pain at PMB BD Itoh in 2023 Research Methods: This type of research used quasi-experimental (quasi-experimental) with the Pre and Posttest Two Group design approach and the samples in this study were 30 mothers who gave birth who met the inclusion criteria and were divided into 15 people as the intervention group and 15 people as the control group with total sampling technique and bivariate analysis using the Dependent T test. Research Results: From the results of the dependent t test that there is a difference with the p value (0.000 <0.05). This concluded that Ho was rejected and Ha was accepted, so that it can be concluded that statistically the respondents had differences in the intensity of pain in labor before and after the rebozo technique at PMB BD Itoh in 2023. From the results of the dependent t test that there is a difference with the p value (0.001 <0.05). This concludes that Ho is rejected and Ha is accepted, so that it can be concluded that statistically there are differences in the intensity of pain in labor before and after the breathing relaxation technique at PMB BD Itoh in 2023. Conclusion: It can be concluded that the mean in the intervention group, namely the Rebozo technique, is more effective than the mean in the control group in reducing the scale of labor pain at PMB BD Itoh in 2023.